Effects of Body Postures on Clothing Air Gap in Protective Clothing (Journal of Fiber Bioengineering and Informatics, 2018)
Air gaps layer between clothing and wearer's body plays an important role in heat transfer in protectiveensembles. The distribution and size of these air gaps are used to determine thermal performance of theprotective clothing, which are dependent not only on garment style and fit but also on all kind of shapesof body motions. In this paper a three dimensional (3D) body scanning technique was used to scan thesurface of the nude and the dressed that can measure accurately the distribution and size of air gapsbetween the human body and clothing. In leg-upright, leg-lifting and leg-withdrawing positions thatsimulated the human motion of running, the clothing air gaps were scanned and measured respectively.A new method for the measurement of air gaps was used, which can reasonably reflect the size betweenthe fabric and the corresponding test sensor. The results show that clothing air gaps are associatedwith body motions. The clothing air gaps vary with the different postures. And the degree of kneejoint flexion affects the deformation of skin and thus the change of air gaps between skin and clothing.The findings can be used to establish heat transfer model to predict thermal performance of protectiveclothing in motion.
Keywords: Air Gaps Layer; Body Posture; 3D Body Scanning; Protective Clothing